Program Tanggungjawab Sosial Korporat “Open Up Your Eyes” - Jamayah, Saili (2018)
KMC 4263 Praktikum Kaunseling (Penyelia: Dr Jamayah Saili) Kuching Autistic Association (KAA), Kuching, Sarawak: 30 Oktober, 2018